TIPOLOGI, DINAMIKA, DAN POTENSI BENCANA ALAM DI KAWASAN PESISIR KABUPATEN TULUNGAGUNG - Anggoro Putranto (Universitas Pakuan, 2020)
This study aims to determine the typology, dynamics and potential of natural disasters in the coastal area of Tulungagung Regency, East Java Province. The results of this study indicate that the typology in the coastal area of Tuluagung Regency consists of structurally shaped coast, wave erosion coast, marine deposition coast, land erosion coast, sub aerial deposition coast and several forms of typology impact from human activities utilizing coastal resources. The form of dynamics that develop in the coastal area of Tulungagung Regency is generally influenced by environmental conditions, factors of sea water waves and human activities in meeting the needs of life as well as for meeting the means of tourism development. While the potential for disasters in the coastal areas of Tulungagung Regency such as tsunami, abrasion, and sea water intrusion.